Emerging azithromycin-resistance among the Neisseria gonorrhoeae strains isolated in Hungary. Issue 1 (December 2016) - Brunner, Alexandra; Nemes-Nikodem, Eva; Jeney, Csaba; Szabo, Dora; Marschalko, Marta; Karpati, Sarolta; Ostorhazi, Eszter
Abstract Background In the 1990s, azithromycin became the drug of choice for many infectious diseases but emerging resistance to the drug has only been reported in the last decade. In the last 5 years, the NationalNeisseria gonorrhoeae Reference Laboratory of Hungary (NNGRLH) has also observed an increased number ofN. gonorrhoeae strains resistant to azithromycin. The aim of this study was to determine the most frequent sequence types (ST) ofN. gonorrhoeae related to elevated levels of azithromycin MIC (minimal inhibitory concentration). Previously and currently isolated azithromycin-resistant strains have been investigated for the existence of molecular relationship. Methods Maldi-Tof technic was applied for the identification of the strains isolated from outpatients attending the reference laboratory. Testing antibiotic susceptibility of azithromycin, cefixime, ceftriaxone, tetracycline, spectinomycin and ciprofloxacin was carried out for all the identified strains, using MIC strip test Liofilchem® .N. gonorrhoeae multiantigen sequence typing (NG-MAST) was performed exclusively on azithromycin-resistant isolates. A phylogenetic tree was drawn using MEGA6 (Molecular Evolutionary Genetics Analysis Version 6.0) Neighbour-Joining method. Results Out of 192N. gonorrhoeae isolates, 30.0 % (58/192) proved resistant to azithromycin (MIC > 0.5 mg/L). Of the azithromycin-resistant isolates, ST1407, ST4995 and ST11064 were the most prevalent. Based on the phylogenetic analysis, the latter two STs are closely related. Conclusions In contrast to West-European countries, in our region, resistance to azithromycin has increased up to 30 % in the last 5 years, so the recommendation of the European Guideline −500 mg of ceftriaxone combined with 2 g of azithromycin as first choice therapy againstN. gonorrhoeae - should be seriously considered in case of Hungary.